Investor irrationality and closed-end hedge funds - Heinz Zimmermann; Oliver Dietiker (Universität Basel, Wirtschaftswissenschaftliches Zentrum (WWZ), 2009)
This study questions the rationality of people investing in HFs. I use a sample of London listed closed-end hedge funds to evaluate two criteria that imply irrational behavior. I find that the rationality of investors can not be rejected for the majority of time. However, the results also imply that investors react irrationally when facing the worsening economic conditions in the second half of 2008.
Keywords: 330; Hedgefonds; Anlageverhalten; Rationalität; Schätzung; London